Non-Material Factors of the Innovation Activity - Наталья Юрьевна Фирсова (Journal of Economic Sociology, 2010)
The goal of the study is to identify the existence and the character of the interdependence between the innovativeness in everyday life (on example of leisure and consumption practices) and individual characteristics and household characteristics to which a person belongs to. In other words to analyze the link between innovation practices and income, age, gender, family type, education and place of living (capital or other city). Empirical basis for the research was the survey conducted within the project “Economic and social strategies of the middle class” in November 2000, which is representative for the whole Russia and regional city-centers.